2006
DOI: 10.1109/lcomm.2006.02013.
|View full text |Cite
|
Sign up to set email alerts
|

Broadcast capacity of wireless networks

Abstract: Abstract-A fundamental problem in wireless networks is determining the broadcast capacity, i.e. the maximum data transfer rate from a given node to every other node in a relay network. This problem becomes more important as many network protocols rely on broadcast of certain control messages. In this paper, the scaling of the broadcast capacity with the number of nodes (N ) in the network is studied. In the highdensity regime (i.e. the node density goes to infinity; the network area is fixed), it is shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 15 publications
5
49
0
Order By: Relevance
“…Tavli [2] showed that Θ(n −1 ) is an upper bound per node broadcast capacity in an arbitrary network. Zheng [3] studied the behavior of information dissemination in powerconstrained wireless networks in terms of the broadcast capacity and information diffusion rate in both random extended and dense networks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Tavli [2] showed that Θ(n −1 ) is an upper bound per node broadcast capacity in an arbitrary network. Zheng [3] studied the behavior of information dissemination in powerconstrained wireless networks in terms of the broadcast capacity and information diffusion rate in both random extended and dense networks.…”
Section: Related Workmentioning
confidence: 99%
“…Recent research activities focused on the capacity of wireless ad hoc networks for different types of information dissemination such as unicast, broadcast (e.g., [2]- [4]) and multicast (e.g., [5]- [7]). Computation of all kinds of information dissemination plays an important role in understanding the fundamental limits of wireless ad hoc networks.…”
Section: Introductionmentioning
confidence: 99%
“…A connected dominating 2 In this paper, we assume receiver range is equal to transmission range set (CDS (R(n))) is a dominating set such that the subgraph induced by its nodes is connected. A Minimum Connected Dominating Set (MCDS (R(n))) is a CDS(R(n)) of G with the minimum number of nodes.…”
Section: Definition 23: Minimum Connected Dominating Set (Mcds (R(n)))mentioning
confidence: 99%
“…Since then, researchers have studied the throughput capacity of wireless ad hoc networks for multicast and broadcast communication [2]- [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation